Resilience with Work Stress on Bank Employees - Glorya Maharani Clarhend Noach; M. K. P. Abdi Keraf; Diana Aipipidely (Universitas Nusa Cendana, 2023)
This research is a study conducted to determine the correlation between resilience and work stress on employees of PT Bank Pembangunan Daerah Nusa Tenggara Timur . Resilience is a person's ability to cope with anxiety, stress and the consequences of stress. This type of research is quantitative. The number of participants in this study were 179 employees of the head office of PT Bank Pembangunan Daerah Nusa Tenggara Timur using purposive sampling. Data collection used two scales, namely the Work Stress Scale with the results of the reliability test using Cronbach's alpha of 0.850. And the resilience scale with the results of the Cronbach's alpha reliability test is 0.894. Based on the results of the Spearman rank correlation test, it is known that the significant value is 0.000 <0.05 so that it can be said that there is a correlation between work stress and resilience, and based on the value of the correlation coefficient (r ) - 0.473 it can be said that work stress and resilience have a negative correlation.